Effect of clarithromycin on the production of volatile fatty acids from waste activated sludge anaerobic fermentation. (September 2019) - Huang, Xiaoding; Xu, Qiuxiang; Wu, Yanxin; Wang, Dongbo; Yang, Qi; Chen, Fei; Wu, You; Pi, Zhoujie; Chen, Zhuo; Li, Xiaoming; Zhong, Qiong
Graphical abstract: Highlights: Clarithromycin promoted volatile fatty acids production from sludge fermentation. Clarithromycin was partly degraded during the anaerobic fermentation process. Clarithromycin enhanced sludge solubilization process. Clarithromycin inhibited all the other process of anaerobic fermentation. Abstract: This study investigated the effect of Clarithromycin (CLA) on volatile fatty acids (VFAs) production during waste activated sludge (WAS) anaerobic fermentation for the first time. Experimental results showed that when CLA concentration in WAS increased from 0 to 1000 mg/kg TSS, the maximum yield of VFAs increased from 27.7 to 35.7 mg COD/g VSS (without pH pretreatment) and from 59.3 to 65.6 mg COD/g VSS (initial pH 9 pretreatment), respectively. Mechanism exploration revealed that CLA facilitated the disruption of extracellular polymeric substances, thus promoting WAS solubilization. CLA inhibited all the other anaerobic fermentation processes. However, its inhibition to acetogenesis and methanogenesis was severer than that to hydrolysis and acidogenesis, resulting in the decrease in VFAs consumption. Microbial analysis showed that CLA slightly increased the abundance of microorganisms responsible for hydrolysis and acidogenesis whereas decreased the proportion of VFAs-consuming microorganisms.